2021
DOI: 10.3390/pharmaceutics13020288
|View full text |Cite
|
Sign up to set email alerts
|

Suprachoroidal Delivery of Small Molecules, Nanoparticles, Gene and Cell Therapies for Ocular Diseases

Abstract: Suprachoroidal drug delivery technology has advanced rapidly and emerged as a promising administration route for a variety of therapeutic candidates, in order to target multiple ocular diseases, ranging from neovascular age-related macular degeneration to choroidal melanoma. This review summarizes the latest preclinical and clinical progress in suprachoroidal delivery of therapeutic agents, including small molecule suspensions, polymeric entrapped small molecules, gene therapy (viral and nonviral nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 106 publications
0
51
0
Order By: Relevance
“…Suprachoroidal delivery can target therapy to affected chorioretinal tissues for potential efficacy benefits, compartmentalizing it away from unaffected vitreous and anterior segment tissues for potential safety benefits, and achieve durability through the use of insoluble suspension formulations. 65 This approach was assessed with proof of concept therapy, CLS-TA or Xipere, a proprietary suspension of triamcinolone, for uveitic macular edema, culminating in a successful phase 3 clinical trial; durability was demonstrated in an extension study, with a new drug application planned for 2021. 66 In preclinical studies of axitinib, compared to intravitreal administration, suprachoroidal administration resulted in much greater targeted levels of axitinib in retinal and choroidal tissues, with lower levels in the vitreous and anterior segment, which could minimize the risk of off-target effects.…”
Section: Sustained Delivery Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suprachoroidal delivery can target therapy to affected chorioretinal tissues for potential efficacy benefits, compartmentalizing it away from unaffected vitreous and anterior segment tissues for potential safety benefits, and achieve durability through the use of insoluble suspension formulations. 65 This approach was assessed with proof of concept therapy, CLS-TA or Xipere, a proprietary suspension of triamcinolone, for uveitic macular edema, culminating in a successful phase 3 clinical trial; durability was demonstrated in an extension study, with a new drug application planned for 2021. 66 In preclinical studies of axitinib, compared to intravitreal administration, suprachoroidal administration resulted in much greater targeted levels of axitinib in retinal and choroidal tissues, with lower levels in the vitreous and anterior segment, which could minimize the risk of off-target effects.…”
Section: Sustained Delivery Treatmentsmentioning
confidence: 99%
“… 66 In preclinical studies of axitinib, compared to intravitreal administration, suprachoroidal administration resulted in much greater targeted levels of axitinib in retinal and choroidal tissues, with lower levels in the vitreous and anterior segment, which could minimize the risk of off-target effects. 65 …”
Section: Sustained Delivery Treatmentsmentioning
confidence: 99%
“…It is an invasive route and causes difficulty to patients, but alternative clinical outcomes are bleak at present [ 4 , 5 ]. Various administrative routes are explored, such as periocular, suprachoroidal, sub-retinal, systemic, and topical routes for the delivery of small molecules, biologics, and gene therapy [ 6 ]. Molecular therapies such as cell therapy and gene therapy are in focus due to their restoration ability [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment non-compliance can worsen the overall prognosis of RVDs by breaking the necessary continuation of treatment required to keep neovascularization in check 6 . However, recent developments in small molecule anti-angiogenic drugs provide potential treatments for these RVDs that could utilize less invasive drug delivery systems, such as eye drops, oral tablets, and subconjunctival or suprachoroidal injections 7 10 . Non-invasive treatment options also avoid the rare but serious risks of adverse events with IVT injections, notably endophthalmitis 11 .…”
Section: Introductionmentioning
confidence: 99%